1986
DOI: 10.1111/j.1399-3054.1986.tb02447.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing differences in relative growth rate: A method avoiding curve fitting and pairing

Abstract: . 1986. Testing differences in relative growth rate: A method avoiding curve fitting and pairing. -Physiol. Plant. 67: 223-226.A method is discussed to test differences in relative growth rates. This method is based on an analysis of variance, with ln-transformed plant weight as dependent variable. A significant Group × Time interaction indicates differences in relative growth rates between groups. The advantages over the "classical" and "functional" growth analyses are: (1) No pairing procedure is required. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 6 publications
0
95
0
Order By: Relevance
“…For each replicate chamber, mean dry weights were calculated for five observations within a harvest. An ANOVA was performed according to Poorter & Lewis (1986). A trend analysis over plant age was conducted with data partitioned using orthogonal contrasts; this approach allowed examination of the nature of changes in RGR, i.e., linear, quadratic and cubic.…”
Section: Discussionmentioning
confidence: 99%
“…For each replicate chamber, mean dry weights were calculated for five observations within a harvest. An ANOVA was performed according to Poorter & Lewis (1986). A trend analysis over plant age was conducted with data partitioned using orthogonal contrasts; this approach allowed examination of the nature of changes in RGR, i.e., linear, quadratic and cubic.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that a significant interaction between [CO # ] and time occurred, which is more complex than this analysis can elucidate. On the other hand, the significant quadratic component of the interaction between temperature regime and time indicates that there was a positive effect of temperature regime on RGR, which changed linearly with time (Poorter & Lewis, 1986). Fits of instantaneous RGR against time showed that a positive correlation of RGR with temperature regime occurred in the beginning of the experiment, which then vanished (data not shown).…”
Section: Effects Of Temperature Regime and [Co # ] On Growth During Tmentioning
confidence: 95%
“…The log etransformed dry weights were used as dependent variables (Poorter & Lewis, 1986). By this method the interactions of [CO # ] with time or temperature with time were partitioned into orthogonal contrasts with linear and quadratic components (Sokal & Rohlf, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence of significant differences in  between healthy and infected plants was evaluated per species and nutrient treatment by testing with s the effect of the plant statusitime interaction on the log e -transformed plant weight (Poorter & Lewis, 1986).…”
Section: Discussionmentioning
confidence: 99%